A Fatal Poisoning from an Amatoxin Containing Lepiota - J. H. Haines; Lichstein, E.; Glickerman, D. (Mycopathologia, 1986)
The mushroom Lepiota josserandii Bon and Boif. has been identified as the cause of an unintentional, fatal intoxication in New York. The course of the symptoms, beginning with a 9 h latent period, was similar to what would be expected in a case of Amanita phalloides-type intoxication. Despite supportive medical care the victim expired 110 h after ingestion. Thin layer chromatography detected the presence of alpha- and gamma-amanitin and radioimmunoassay confirmed a level of 3.5 mg/gm dry weight of amatoxins in mushrooms from the same location.
Keywords: biology